2013
DOI: 10.1093/gbe/evt027
|View full text |Cite
|
Sign up to set email alerts
|

Replicon-Dependent Bacterial Genome Evolution: The Case of Sinorhizobium meliloti

Abstract: Many bacterial species, such as the alphaproteobacterium Sinorhizobium meliloti, are characterized by open pangenomes and contain multipartite genomes consisting of a chromosome and other large-sized replicons, such as chromids, megaplasmids, and plasmids. The evolutionary forces in both functional and structural aspects that shape the pangenome of species with multipartite genomes are still poorly understood. Therefore, we sequenced the genomes of 10 new S. meliloti strains, analyzed with four publicly availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
114
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(128 citation statements)
references
References 92 publications
(125 reference statements)
12
114
0
2
Order By: Relevance
“…However, the evolution of these symbiosis-related genes, other than the nod and nif genes, is largely unknown. Sinorhizobium genomes are characterized by the presence of three main replicons (a chromosome; a chromid, pSymB; and a megaplasmid, pSymA), and nif and most nod genes are located on pSymA (68)(69)(70)(71). In this study, we investigated the evolution of nod genes involved in regulation (nodD1 and nodD2 on pSymA), biosynthesis of the glucosamine (chitin) oligosaccharide backbone (nodC on pSymA and nodM on the chromosome), and modification (nodS on pSymA) and biosynthesis of fatty acyl at the nonreducing termini (nodE on the chromosome) of Nod factors (72).…”
Section: Discussionmentioning
confidence: 99%
“…However, the evolution of these symbiosis-related genes, other than the nod and nif genes, is largely unknown. Sinorhizobium genomes are characterized by the presence of three main replicons (a chromosome; a chromid, pSymB; and a megaplasmid, pSymA), and nif and most nod genes are located on pSymA (68)(69)(70)(71). In this study, we investigated the evolution of nod genes involved in regulation (nodD1 and nodD2 on pSymA), biosynthesis of the glucosamine (chitin) oligosaccharide backbone (nodC on pSymA and nodM on the chromosome), and modification (nodS on pSymA) and biosynthesis of fatty acyl at the nonreducing termini (nodE on the chromosome) of Nod factors (72).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the chromosome is enriched for genes with cell cycle-regulated expression, an inference that was verified by a hypergeometric test (P < 0.001). The especially low percentage of genes demonstrating cell cycle-regulated transcription on pSymA compared with the chromosome and pSymB could be a result of pSymA being a more recently acquired, less domesticated replicon than pSymB (6,31).…”
Section: Microarray Analysis Of Synchronized S Meliloti Cultures Idementioning
confidence: 99%
“…Some correspondence between the geographic area of isolation and genetic differentiation among 14 completely sequenced S. meliloti strains was recently shown at the genome level as well [23]. These studies support a role for geographic distance in influencing genetic diversity, at least within large geographic areas where distances are measured as hundreds of km; however, few investigations have been performed on the biogeographic pattern of S. meliloti genotypes in a more restricted geographic range [14] where distances are less than 50 km.…”
Section: Introductionmentioning
confidence: 79%
“…Sinorhizobium meliloti is distributed world-wide in many soils, both at temperate latitudes and in subtropical zones, in symbiotic association with legumes [1], in endophytici (mutualistic) associations [46,9] and in a free-living form [7,12]. This species is a model for studying legume-rhizobia symbiosis and symbiotic nitrogen fixation [26], and is one of the most thoroughly investigated at the genome level among rhizobia [15,22,23,54]. Population genetics of this species has also been widely investigated and showed that strains of S. meliloti (as well as of its sister species Sinorhizobium medicae) are highly variable; consequently, various studies have explored the relationship between the pattern of genetic variation and environmental factors [2,8,30,44,45,55,58].…”
Section: Introductionmentioning
confidence: 99%